Prenatal care: Complementary examinations and their importance (Research, Society and Development, 2024)
The proper implementation of prenatal care promotes the healthy development of the baby and allows for the early detection of maternal and fetal diseases, reducing the risks of obstetric complications. In this sense, the complementary tests used in the clinical practice of prenatal care significantly contribute to the assessment of the health of both the mother and the baby, help prevent and identify diseases early, and decrease the chances of mortality during pregnancy. This study aimed to identify the importance of prenatal follow-up and the understanding of the main tests requested in outpatient prenatal care. To achieve this, an exploratory integrative literature review was conducted based on studies published in the last six years and manuals from 2012 and 2014 that addressed the researched topic and were available electronically in their full format. The main tests to be conducted in the clinical practice of monitoring pregnancy are: β-HCG, complete blood count, blood typing and indirect Coombs test, serologies for infectious diseases, TSH, fasting glucose, oral glucose tolerance test, and ultrasounds. Thus, it is of utmost importance to carry out these tests in conjunction with regular prenatal care to ensure comprehensive and qualified assistance and to provide maternal-fetal safety.